Computer aided process engineering (CAPE) - Kamsah, Mohd Zaki (Jawatankuasa Penyelidikan & Perundingan, Fakulti Kej. Kimia & Kej. Sumber Asli, UTM, 1992)

(untitled)
The advancement of information technology has the potential to significantly alter the operation and training operators in the chemical industries. From early 1980s, large computer-aided process design packages became available for installation on mainframe computers. Most recently, many commercial softwares are available on personal computers and they can also be utilized to enhance and simplify the learning methods. But all the softwares and technologies are either developed in foreign countries or developed locally by foreign experts. A study was carried out in the development of packages for computer-based training (CBT) to be used by the local process industries for better operation in plants and effective training for safety. CBT is well received in all sectors of enterprises that involve training for safety. CBT is well received in all sectors of enterprises that involve training of all levels of staff from managers down to the operators. Three modules have been identified in the study-simulation, multimedia and chemical properties.